2018
DOI: 10.1017/s0007485318000366
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific aggregation pheromones contribute to coexistence in two closely related thrips species

Abstract: Pheromones play an important role in mediating interspecific interactions in insects. In an insect community, pheromones can reveal information about the senders, which could be used by other members of the food web (competitor, natural enemies, etc.) to their own advantage. The aggregation pheromones of two closely related thrips species, Frankliniella occidentalis and Frankliniella intonsa, have been identified with the same major compounds, (R)-lavandulyl acetate and neryl (S)-2-methylbutanoate, but in diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 39 publications
(50 reference statements)
0
15
0
Order By: Relevance
“…The function of ( R )‐lavandulyl acetate may be related to mediating interspecific interactions of F. occidentalis and other related thrips. In fact, it has recently been reported that this compound mediates the aggregation of F. occidentalis and Frankliniella intosa (Geng, Li, Zhang, Zhang, & Lu, 2017; Li et al., 2019). However, when both species do not coexist, it seems that ( R )‐lavandulyl acetate is not necessary to attract F. occidentalis (Kirk, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The function of ( R )‐lavandulyl acetate may be related to mediating interspecific interactions of F. occidentalis and other related thrips. In fact, it has recently been reported that this compound mediates the aggregation of F. occidentalis and Frankliniella intosa (Geng, Li, Zhang, Zhang, & Lu, 2017; Li et al., 2019). However, when both species do not coexist, it seems that ( R )‐lavandulyl acetate is not necessary to attract F. occidentalis (Kirk, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Characteristic species-specific ratios of major to minor compounds have been recorded in F. occidentalis and F. intonsa (Zhang et al 2011 ; Zhu et al 2012 ), although these ratios can change during the day (Li et al 2017 ). Field trials in China have recently shown a differential catch between the two species with two different compound ratios (Li et al 2018 ), suggesting the two compounds are components of one pheromone. However, field trials in Spain with F. occidentalis , using a range of release rates and ratios, did not find a ratio that caught more than the major compound alone (Dublon 2009 ; Sampson 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the indistinguishable species belonging to thrips, Megalurothrips usitatu s (Bagnall) and Frankliniella intonsa (Trybom), two of the most common flower‐dwelling thrips, currently have caused huge damage to a wide range of leguminous crops throughout the world 20,21 . As two closely related thrips, M. usitatus and F. intonsa share a number of similarities, including biological traits, occurrence pattern and behavior habits 22,23 . The two devastating thrips have posed an increasing threat to the cowpea industry in China, 23,24 leading to large economic losses through yield reductions and management costs.…”
Section: Introductionmentioning
confidence: 99%